2006
DOI: 10.1086/505399
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus: Prevalence and Clinical Spectrum at a Children’s Hospital

Abstract: HBoV DNA is commonly present in children with upper and lower respiratory tract infections. The presence of a pertussis-like cough and diarrhea in association with HBoV infection merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
213
12
30

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(284 citation statements)
references
References 14 publications
29
213
12
30
Order By: Relevance
“…Although IgG antibody present in a single serum sample does not reflect an acute infection, a high rate of IgG positive sera from healthy children does suggest that HBoV infection is more common in children than genomic detection has shown previously (Allander et al, 2005;Arnold et al, 2006;Bastien et al, 2006;Choi et al, 2006;Foulongne et al, 2006;Lin et al, 2007;Ma et al, 2006;Qu et al, 2007;Sloots et al, 2006;Weissbrich et al, 2006). Infection with B19 occurs in children in a high incidence asymptomatically.…”
Section: Discussionmentioning
confidence: 92%
“…Although IgG antibody present in a single serum sample does not reflect an acute infection, a high rate of IgG positive sera from healthy children does suggest that HBoV infection is more common in children than genomic detection has shown previously (Allander et al, 2005;Arnold et al, 2006;Bastien et al, 2006;Choi et al, 2006;Foulongne et al, 2006;Lin et al, 2007;Ma et al, 2006;Qu et al, 2007;Sloots et al, 2006;Weissbrich et al, 2006). Infection with B19 occurs in children in a high incidence asymptomatically.…”
Section: Discussionmentioning
confidence: 92%
“…Control group participants were children <18 years of age (median Clinical data were obtained by using standardized forms to extract data from electronic charts. Underlying illnesses were defi ned as chronic pulmonary disease, congenital heart disease, immunodefi ciency, malignancy, neurologic disease, or gastrointestinal disease (8). To assess the severity of illness, we used the lowest ratio during the fi rst 24 hours of the partial pressure of oxygen in arterial blood (PaO 2) to the inspired oxygen fraction (FiO 2 ).…”
Section: The Studymentioning
confidence: 99%
“…Most prevalence studies were done on samples from children with respiratory tract diseases, with rates observed between 1.5-19% (1,(4)(5)(6)(7)(8)(9)(10)(11)(12). Studies made on fecal specimens indicate that HBoV is also prevalent in children with acute gastroenteritis, with 0.8-16% of samples being HBoV + (4,(13)(14)(15). In addition, HBoV infection with complex clinical conditions in immunosuppressed patients has been suggested (16).…”
mentioning
confidence: 99%